Endocrine Gland-Derived Vascular Endothelial Growth Factor/Prokineticin-1 in Cancer Development and Tumor Angiogenesis - Ana Silvia Corlan; Anca Maria Cîmpean; Adriana-Andreea Jitariu; Eugen Melnic; Marius Raica (International Journal of Endocrinology)
A lot of data suggests endocrine gland-derived vascular endothelial growth factor (EG-VEGF) to be restricted to endocrine glands and to some endocrine-dependent organs. Many evidences show that EG-VEGF stimulates angiogenesis and cell proliferation, although it is not a member of the VEGF family. At the time, a lot of data regarding the role of this growth factor in normal development are available. However, controversial results have been published in the case of pathological conditions and particularly in malignant tumors. Thus, our present paper has been focused on the role of EG-VEGF in normal tissues and various malignant tumors and their angiogenic processes.